2017
DOI: 10.1590/1983-21252017v30n103rc
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matter Labile Fractions and Carbon Stocks in a Typic Quartzipsamment Cultivated With Sugarcane Harvested Without Burning

Abstract: -The permanence of sugarcane straw on the soil surface, in systems without the pre-harvest straw burning practice, directly affects the soil organic matter dynamics. The objective of this work was to evaluate the changes in total organic carbon (TOC), carbon in the light organic matter (CLOM) and particulate organic carbon (POC), and their carbon stocks in a typic Quartzipsamment cultivated for nine years with sugarcane crops, which were conducted without the pre-harvest straw burning practice, in Paraipaba, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Almost all the organic carbon in eucalyptus harvest residue management is particulate organic carbon (POC) (Table 3). This proportion of POC is higher than that obtained in a study carried out by Oliveira Filho et al [59] in forest and sugarcane areas under Quartzarenic Neosol, who observed that approximately 60% of total organic C is in the form of POC. This difference between the results may be related to the fact that their study presented clay contents six times greater than in our study, which could favor a higher stabilization of C in the mineral fraction of the soil.…”
Section: Discussioncontrasting
confidence: 73%
“…Almost all the organic carbon in eucalyptus harvest residue management is particulate organic carbon (POC) (Table 3). This proportion of POC is higher than that obtained in a study carried out by Oliveira Filho et al [59] in forest and sugarcane areas under Quartzarenic Neosol, who observed that approximately 60% of total organic C is in the form of POC. This difference between the results may be related to the fact that their study presented clay contents six times greater than in our study, which could favor a higher stabilization of C in the mineral fraction of the soil.…”
Section: Discussioncontrasting
confidence: 73%
“…Loss et al (2010) also found the highest CLOM values at a depth of up to 10 cm, for areas under Forest-pasture System, indicating a more complex organic material for decomposition. According to Oliveira Filho et al (2017), the high similarity between CMOL and Total Carbon (TC) may explain the low response of CMOL in identifying changes in Organic Matter (OM) between the areas assessed, in addition to indicating a high dependence on CMOL in the content fraction of TC.…”
Section: Carbon and Nitrogen Stocksmentioning
confidence: 99%
“…One of the more specific ways of assessing total organic carbon (TOC), and consequently the effect of land use and management practices on soil quality is related to the evaluation of the light organic matter (LOM). LOM is the active fraction in the soil, composed of organic residues at different decomposition stages, and can vary rapidly with changes in soil management, depending on the recalcitrance of the original material, and influence the soil chemical quality [13]. LOM can be considered as accelerated dynamics in the soil, among SOM compartments [14].…”
Section: Introductionmentioning
confidence: 99%